Improving Cerebrovascular Function to Increase Neuronal Recovery in Neurodegeneration Associated to Cardiovascular Disease - Vanherle, Lotte; Matuskova, Hana; Don-Doncow, Nicholas; Uhl, Franziska E.; Meissner, Anja (Frontiers in Cell and Developmental Biology, 2020)
Mounting evidence indicates that the presence of cardiovascular disease (CVD) and risk factors elevates the incidence of cognitive impairment (CI) and dementia. CVD and associated decline in cardiovascular function can impair cerebral blood flow (CBF) regulation, leading to the disruption of oxygen and nutrient supply in the brain where limited intracellular energy storage capacity critically depends on CBF to sustain proper neuronal functioning. During hypertension and acute as well as chronic CVD, cerebral hypoperfusion and impaired cerebrovascular function are often associated with neurodegeneration and can lead to CI and dementia. Currently, all forms of neurodegeneration associated to CVD lack effective treatments, which highlights the need to better understand specific mechanisms linking cerebrovascular dysfunction and CBF deficits to neurodegeneration. In this review, we discuss vascular targets that have already shown attenuation of neurodegeneration or CI associated to hypertension, heart failure and stroke by improving cerebrovascular function or CBF deficits.